Synthesis of Binderless ZK-4 Zeolite Microspheres at High Temperature - Elyssa G. Fawaz; Darine A. Salam; Habiba Nouali; Irena Deroche; Severinne Rigolet; Benedicte Lebeau; T. Jean Daou (Molecules, 2018)
Binderless zeolite macrostructures in the form of ZK-4 microspheres were prepared using anion-exchange resin beads as shape-directing macrotemplates. The particles were synthesized under hydrothermal conditions at different temperatures and treatment times. The influence of the different synthesis parameters was investigated by X-ray diffraction, scanning electron microscopy, fluorescence X, nitrogen adsorption measurements and 29Si solid-state NMR. Fully crystalline spheres similar in size and shape to the original resin beads were obtained by a hydrothermal treatment at the highest temperatures (150–180 °C) for a short treatment time of 24 h. The synthesized microspheres showed to be promising in the molecular decontamination of volatile organic compounds (VOCs).